Assessment of three types of surgical procedures for supravalvar aortic stenosis: A systematic review and meta-analysis - Lv, Lizhi; Lang, Xinyue; Zhang, Simeng; Wang, Cheng; Wang, Qiang (Frontiers in Cardiovascular Medicine, 2022)
Importance: The safety and efficacy of different surgical repairs of supravalvar aortic stenosis (SVAS) are inconsistent. Objective: To compare the prognosis of single-, two- and three-patch repair for patients with SVAS. Data sources: PubMed, EMBASE, Cochrane Library, Web of Science, and clinicaltrials.gov were searched until April 17, 2022. Study selection: Study reported SVAS patients treated with single-, two- or three-patch repair. Data extraction and synthesis: Two reviewers independently extracted the data of study characteristics and clinical outcomes. Multiple pairwise and frequentist network meta-analyses were conducted. And a fixed-effect model was used when no heterogeneity existed. Main outcomes and measures: Outcomes included the rate of reintervention, aortic insufficiency, early mortality and late mortality, cardiopulmonary bypass (CPB) time, cross-clamping (CCP) time, and postoperative/ follow-up pressure gradient. Binary variables were evaluated by odds ratio (OR) and its 95% confidence interval (CI), while continuous variables were assessed by standardized mean difference (SMD) and its 95% CI. Results: Twenty-seven retrospective cohort studies were included, comprising 1162 patients, undergoing single-patch (46.6% of cases), two-patch (33.9%), and three-patch repair (19.4%). Two-patch method had a lower rate of reintervention compared with single-patch (OR = 0.47, 95 % CI 0.28 to 0.89), and three-patch (OR = 0.31, 95 % CI 0.15 to 0.64). This finding also applied to juvenile and non-Asian patients. Three-patch method had a lower rate of aortic insufficiency compared with single-patch (OR = 0.11, 95 % CI 0.01 to 0.63), and two-patch (OR = 0.11, 95 % CI 0.02 to 0.83). But this repair had the longest CCP time, which was significantly longer than that of single- (SMD = 0.76, 95 % CI 0.36 to 1.17) or two-patch repair (SMD = 0.61, 95 % CI 0.06 to 1.16). No significant difference was found in mortality and pressure gradient among three procedures. Conclusion and relevance: Two-patch repair has the lowest reintervention rate and relatively reasonable operation time. Complex and severe SVAS is suggested to be treated with two-patch repair. Further prospective studies of a reasonable sample size will be required with a special focus on the use of different patch materials and surgeons’ unique working experience.